Classifications of compound words in multi-language systems (Eurasian Journal of Philology Science and Education, 2019)
This article examines the different scientific approaches and classifications of compound words inmultilanguage systems, as well as the basic methods of word formation in German, the methods ofwriting compound words, features, difficulties and rules for translating complex, multipart words onGerman vocabulary examples. The purpose of this work is defining relations of complex names andisomorphic free word combinations on the basis of existing most acceptable criteria for selecting complex words, as well as the analyzing the structure of complex names and the establishment of their basicstructural types and wordformation models. The article reviews the domestic and foreign literature onthe considered problem, including reviews of domestic scientists on grammatical categories. The studiesexamined allowed us to determine the main directions, ideas and concepts in the study of this conceptions and to determine the prospects for further research.